2015
DOI: 10.1002/mnfr.201400660
|View full text |Cite
|
Sign up to set email alerts
|

The effects of methyl-donor deficiency on the pattern of gene expression in mice

Abstract: The results of our study provide a plausible explanation of why diets lacking methyl donors can induce the development of liver cancers in rodents and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…Although studies have established that folate deficiency diet affected the gene expression pattern in many organs, including the liver, kidney, spleen, and testis, in mice[7, 10, 34], to our knowledge, the present study reported for the first time that folate deficiency altered the amount of several mRNAs in the human sperm. Because of the loss of the transcription ability of mature sperm, the effect of folate deficiency may arise in the early stage of spermatogenesis.…”
Section: Discussioncontrasting
confidence: 50%
“…Although studies have established that folate deficiency diet affected the gene expression pattern in many organs, including the liver, kidney, spleen, and testis, in mice[7, 10, 34], to our knowledge, the present study reported for the first time that folate deficiency altered the amount of several mRNAs in the human sperm. Because of the loss of the transcription ability of mature sperm, the effect of folate deficiency may arise in the early stage of spermatogenesis.…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies have reported gene expression changes at the transcriptomic level in the liver of rodents in response to diets low in folate [33,34,35]. Although several aspects of design differ between studies (summarised in Table 10), to identify a key set of genes in the liver that respond to changes in folate intake (or more broadly, changes in one carbon metabolism), we compared reported changes in gene expression between our data and three other studies [33,34,35].…”
Section: Resultsmentioning
confidence: 99%
“…Although several aspects of design differ between studies (summarised in Table 10), to identify a key set of genes in the liver that respond to changes in folate intake (or more broadly, changes in one carbon metabolism), we compared reported changes in gene expression between our data and three other studies [33,34,35]. Of the 989 genes which were differentially expressed in the fetal liver in response to maternal folate depletion in our study, 4, 89, 90 and 239 genes were also found to be differentially expressed in CBA mice, BALB/c mice, CBA/Ca mice and Wistar rats respectively [33,34,35] (full list of these genes for individual studies are in Supplementary Materials Table S6). Comparison of the differentially expressed genes from all studies revealed a set of 21 key genes whose expression was affected by altered folate/methyl donor intake in at least four of the five data sets (see Table 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, high quality RNA extraction and gene pattern analyses have previously been illustrated in non-exposed offspring of irradiated CBA/Ca and BALB/c male mice (Gomes et al, 2015) as well as in CBA/Ca and BALB/c mice subjected to a methyl-donor deficient diet (Glen et al, 2015). RNAs were therefore extracted from both kidneys in each mouse per exposure group and quality analysis performed (Chapter 2.13.1, Figure 10).…”
Section: Experimental Designmentioning
confidence: 99%